SnS2/Sb2S3 Heterostructures Anchored on Reduced Graphene Oxide Nanosheets with Superior Rate Capability for Sodium‐Ion Batteries. Issue 15 (16th February 2018) - Wang, Shijian; Liu, Shuaishuai; Li, Xuemei; Li, Cong; Zang, Rui; Man, Zengming; Wu, Yuhan; Li, Pengxin; Wang, Guoxiu
Abstract: Tin disulfide, as a promising high‐capacity anode material for sodium‐ion batteries, exhibits high theoretical capacity but poor practical electrochemical properties due to its low electrical conductivity. Constructing heterostructures has been considered to be an effective approach to enhance charge transfer and ion‐diffusion kinetics. In this work, composites of SnS2 /Sb2 S3 heterostructures with reduced graphene oxide nanosheets were synthesized by a facile one‐pot hydrothermal method. When applied as anode material in sodium‐ion batteries, the composite showed a high reversible capacity of 642 mA h g −1 at a current density of 0.2 A g −1 and good cyclic stability without capacity loss in 100 cycles. In particular, SnS2 /Sb2 S3 heterostructures exhibited outstanding rate performance with capacities of 593 and 567 mA h g −1 at high current densities of 2 and 4 A g −1, respectively, which could be ascribed to the dramatically improved Na + diffusion kinetics and electrical conductivity. Abstract : Heterostructured electrode : Composites of SnS2 /Sb2 S3 heterostructures with reduced graphene oxide (rGO) nanosheets were synthesized by a facile one‐pot hydrothermal method. The SnS2 /Sb2 S3 heterostructures show fast Na + diffusion kinetics, and the SnS2 /Sb2 S3 @rGO composites exhibit superior rate performance when used as anodes for sodium‐ion batteries (see figure).